Klassning av renbete med hjälp av ståndortsboniteringens vegetationstypsindelning - Thun, Anna-Karin (2005)
During thousands of years, reindeer have adapted to living under harsh conditions with large seasonal variations in climate and forage availability. This adaptation implies that body functions and nourishment needs are strongly bound to the season. In the summer the reindeer has to maximize food intake to build up fat and protein reserves for the winter. More than 200 different plant species are included in the reindeer diet, but since reindeer have an unique ability to use the nourishment in lichen, different lichen species make up a large portion of their winter diet in many areas. Fundamental for reindeer husbandry is access to natural grazing during most of the year. This is why it is important to document the locations of the grazing resources for all land users in the area that is used for reindeer management, as well as for the long term planning of land use. During the past several years a new concept has been developed in the reindeer management sector, i. e., the reindeer management plan. It is supposed to be used like a forest management plan, as a planning tool, to give an improved view over the land use of Sámi villages. In a reindeer management plan there is a system to classify various grazing types. However, today there is no connection between grazing types and the ground vegetation types used in forestry to access site index. A transformation between the two systems would allow easier planning of land use and cooperation between reindeer husbandry and forestry. This thesis has concentrated on the possible connection between the grazing types in the forest (13 classes) of the reindeer management plan and the forest classification units used in the site quality class system of Hägglund & Lundmark (1981). The objectives were to: • examine the possibility to directly give the site class according to the site quality class system by using the registrations from the grazing survey of the reindeer management plan • find a "key" to enable a translation between the grazing types of the reindeer ...